Eksplorasi Karakteristik Siswa, Budaya Sekolah, Proses Pembelajaran dan Kompetensi Guru: Studi Kasus di SMA Negeri 1 Sunggal dan MAS YASPI Labuhan Deli - Amandana, Jesica; Rahmadina, Laila; Galang, Izza; Geovani, , Jen; Wantri, Joko; Nurkadri, Nurkadri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Introduction to the school field (PLP) I is the initial stage in the process of introducing the school field to the undergraduate education program. The aim is to observe student characteristics, school culture, learning process and teacher competence. Collecting research data is direct observation and using a questionnaire. The results of this study indicate that there are efforts made in developing student character, implementing a good school culture, carrying out an effective learning process, and having teachers with appropriate competencies. Keywords: Student characteristics; school culture; learning process; teacher competence.